The Implementation of Business Ethics in Educators to Improve the Quality of School Services - Trianto Panji Purnomo; Setyo Riyanto; Sugoni Sugoni (TIJAB (The International Journal of Applied Business), 2021)
The application of business ethics is a very important aspect and needs special attention, because the quality of good school services can be obtained if the application of business ethics runs effectively. The purpose of this study is to determine the relationship of business ethics and teacher work discipline to the quality of school services. The research method in this journal uses a descriptive qualitative approach, with a critical data analysis model based on data collection in the form of library research, namely the research method for collecting and analyzing data and references to texts/literature. Ethics refers to ordinary human conduct on what is permissible and what is not permissible. Discipline is a particular type or pattern of character developed by the habit of performing those acts, which can be formed by training the desired behavior patterns and expected behaviors in an attitude that leads to living performance. Service quality refers to all economic activities that generate results that meet prime expectations, whether physical goods or services (non-physical). Discipline is a particular type or pattern of character developed by the habit of performing those acts, which can be formed by training the desired behavior patterns and expected behaviors in an attitude that leads to living performance. Service quality refers to all economic activities that generate results that meet prime expectations, whether in the form of physical goods or services (non-physical). The results of this study indicate that the application of business ethics is in the high category. In addition, the influence of teacher work discipline on the quality of school services is in the medium category. Based on the research results, there are several recommendations that are needed to improve the effectiveness of quality management, including making continuous improvements and optimizing the total quality management (TQM) approach